Rhabdomyolysis secondary to an accident with marine stingray (Dasyatis family) - Masson,AA (2012)
Whenever humans come in touch with the sea, they become vulnerable to risks, most frequently on account of invading a habitat that belongs to potentially harmful aquatic animals. World literature shows a growing number of incidents in recent years with marine stingrays, despite the fact that these animals only attack when harassed. This report describes an accident in which an amateur fisherman was injured by a marine stingray, probably of the Dasyatis family, on his left forearm. The puncture wound was highly painful and progressed to rhabdomyolysis. It is conjectured that lymphatic drainage, applied in an attempt to reduce edema and its complications, may have contributed to rebound increase in serum creatine kinase levels (CK) and, thus, has exacerbated the intensity of rhabdomyolysis. Therefore, as a measure of caution, lymphatic drainage should not enter current treatment protocols for similar cases, until new studies are performed in order to clarify this issue.